Countering the Clash of Civilization Discourse: A Critical Analysis of Huntington’s Reductive Cultural Argument - Rahim, Ahsan-ur-; Bashir, Alia (The Lighthouse Journal of Social Sciences, 2024)
This paper aims to highlight the cultural fault line in Huntington’s thesis, ‘The Clash of Civilizations’. Huntington proposed his thesis in 1996, after the end of the Cold War, arguing that the conflicts in the contemporary world will be based on the cultural identities. However, this research work presents a counter discourse to this reductive argument in the light of Said’s (1978) idea of identity and argues that culture, solely, is not responsible for the contemporary conflicts in the world. The primary reason for such cultural conflicts is the power politics for which these conflicts are constructed. The research is qualitative in nature. The data have been collected through content analysis method and have been analysed in the light of the idea of identity as proposed by Said (1978). Said argues that identity is a construct and is always associated with power politics. Through analysis and discussion it has been concluded that culture is simply not the reason behind contemporary conflicts, the reason behind these conflicts is power politics, i.e. the establishing of the relations of domination over the weaker groups or nations.